Modernising vocational education and training : fourth report on vocational training research in Europe: background report. Volume 2 - Descy, Pascaline [Mitarbeiter]; Tchibozo, Guy [Mitarbeiter]; Tessaring, Manfred [Mitarbeiter]; Béduwé, Catherine [Mitarbeiter]; Germe, Jean-Francois [Mitarbeiter]; Leney, Tom [Mitarbeiter]; Planas, Jordi [Mitarbeiter]; Poumay, Marianne [Mitarbeiter]; Armstrong, Russel [Mitarbeiter]; Parsons, David J. [Mitarbeiter]; Hughes, Jacqui [Mitarbeiter]; Allison, Chris [Mitarbeiter]; et al. (Office for Official Publications of the European Communities, 2009)
"The series of reports on vocational education and training (VET) research have been published by Cedefop since 1998. The reports give a comprehensive review of current socioeconomic research related and relevant to VET and skill development in Europe, its results and implications for policy and future research. Research reports are a tool for evidence-based policy making. Attention is always paid to the theoretical and methodological foundations of research. Each research report consists of a background report of several volumes with contributions from renowned researchers of which this is one and a synthesis report written by Cedefop experts. Fourth research report: modernising vocational education and training Modernising VET is the overarching theme of the fourth research report. It aims to provide and discuss the evidence-base for the process of enhanced cooperation in VET which sets priorities for reforming VET to contribute to the Lisbon process. Volume 2 addresses various aspects and dimensions of the VET reforms process such as: the training and development of VET teachers and trainers, learning at the workplace, VET for older workers, or the differentiation and diversification of VET and higher education." (BIBB-Doku)
Keywords: T 1.5 International vergleichende Berufsbildungsforschung; S 2.3 Berufsbildungspolitik; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2 Europa; Berufsbildung; Modernisierung; Berufsbildungsforschung; Berufliche Qualifikation; Europäischer Qualifikationsrahmen; Nationaler Qualifikationsrahmen; Europa